2022
DOI: 10.3390/ijms23105541
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral and Contralateral Interactions in Spinal Locomotor Circuits Mediated by V1 Neurons: Insights from Computational Modeling

Abstract: We describe and analyze a computational model of neural circuits in the mammalian spinal cord responsible for generating and shaping locomotor-like oscillations. The model represents interacting populations of spinal neurons, including the neurons that were genetically identified and characterized in a series of previous experimental studies. Here, we specifically focus on the ipsilaterally projecting V1 interneurons, their possible role in the spinal locomotor circuitry, and their involvement in the generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 65 publications
(177 reference statements)
0
6
0
Order By: Relevance
“…I have not included data generated from computational modeling work here. This work is of enormous importance as it provides predictions regarding the detailed synaptic connectivity that is able to account for coordinated locomotion ( Rybak et al, 2015 ; Shevtsova et al, 2015 ; Shevtsova and Rybak, 2016 ; Danner et al, 2019 ; Shevtsova et al, 2020 ; Shevtsova et al, 2022 ). It can thus lead directly to testable hypotheses and the design of experiments which investigate whether the predictions are accurate, however, it should not be taken as fact until tracing experiments prove it to be so.…”
Section: Discussionmentioning
confidence: 99%
“…I have not included data generated from computational modeling work here. This work is of enormous importance as it provides predictions regarding the detailed synaptic connectivity that is able to account for coordinated locomotion ( Rybak et al, 2015 ; Shevtsova et al, 2015 ; Shevtsova and Rybak, 2016 ; Danner et al, 2019 ; Shevtsova et al, 2020 ; Shevtsova et al, 2022 ). It can thus lead directly to testable hypotheses and the design of experiments which investigate whether the predictions are accurate, however, it should not be taken as fact until tracing experiments prove it to be so.…”
Section: Discussionmentioning
confidence: 99%
“…The spinal circuitry in the model includes two RGs (as described above) interacting via a series of commissural interneuronal (CIN) pathways mediated by different sets of genetically identified commissural (V0D, V0V, and V3) and ipsilaterally projecting (V2a) interneurons, as well as some hypothetical inhibitory interneurons (Ini). The organization of these intraspinal interactions was directly drawn from our earlier models [26][27][28][29][30][31][32] that were explicitly or implicitly based on the results of molecular/genetic studies of locomotion in mice or were proposed to explain and reproduce multiple aspects of the neural control of locomotion in these studies. Specifically, V0D and V2a-V0V-Ini pathways secure left-right alternation of RG oscillations during walking and trotting at slow and higher locomotor speeds, respectively 26,27,53 .…”
Section: Model Of the Spinal Locomotor Circuitrymentioning
confidence: 99%
“…Here, we use the term CPG for the spinal circuitry controlling and coordinating all limbs, and the term RG (rhythm generator) for the relatively independent part of the CPG that controls rhythmic movements of a single limb. We consider the CPG as a group of RGs, each controlling a single limb and interacting with each other through commissural and/or propriospinal pathways or circuits 3,[26][27][28][29][30][31][32] .…”
Section: Operation Regimes Of the Spinal Locomotor Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on differential expression of calcium buffering proteins and synaptology this early study proposed a diversity of phenotypes and circuit roles for V1 interneurons. Later electrophysiological and modeling studies showed that V1 interneurons play crucial roles in shaping motor output by modulating locomotor speed, governing flexion-extension at the level of central pattern generator (CPG) half-centers and/or last-order reciprocal inhibition of antagonistic motoneurons, and providing recurrent feedback inhibition of motoneuron firing (Sapir et al, 2004; Zhang et al, 2014; Britz et al, 2015; Falgairolle and O’Donovan, 2019, 2021; Shevtsova et al, 2022). Accordingly, there is significant interest in defining the molecular identity and circuit organization of different subtypes of V1 interneurons.…”
Section: Introductionmentioning
confidence: 99%